PKM Penyuluhan Mal Praktik Kebidanan Di Tinjau Dari Aspek Hukum Bagi Bidan diKabupaten Asahan - Atika Pohan; Erwin Syahputra; Titin Fatimah (Insight Power (Kekuatan Wawasan), 2022)
Midwifery services have been around for a long time. The number of health developments so that there are also many health practices such as midwives. In this case, it is often found or the occurrence of midwifery malpractice is detrimental to the community. According to news reports, many of the practices of certain midwives are not in accordance with the procedures for issuing practice permits, resulting in malpractices that are detrimental to consumers/society. The purpose of this service is to provide counseling to midwives about midwifery practice in terms of legal aspects. The result of this service is that midwives are aware of the dangers of the care provided to patients not in accordance with professional standards and ethics, and there is a change in the behavior of midwives in providing midwifery care after service.Keywords: legal aspects, malpractice, midwifery